European Aid for Trade: Need, merit or self-interest? : a dynamic panel data analysis on what motivates the European donors - Nilsson, Johanna (SLU/Dept. of Economics, 2018)
Aid for Trade has been recognized as a tool to integrate developing coun-tries into the world economy, induce economic growth and lift its people out of poverty. EU and its member states are the biggest donors of Aid for Trade in the world, and one of its biggest advocates, but neither Aid for Trade nor the allocation of the European donors, have been subject for much earlier research. What has been heavily investigated is development aid, where studies have found that aid is allocated according to the needs and merit of the recipient countries, but that the self-interest of the donor tend to outweigh the other motives. This might undermine the effectiveness of aid since it has been suggested that aid is more efficiently and effective if given to poor countries with good policies. This thesis address the gap in research about Aid for Trade, and examine if need, merit or self-interest motivates the European donors. A panel data set is constructed using 142 developing countries and is analysed using OLS regression and fixed effects model. My results indicate that the European donors allocate their Aid for Trade according to individual preferences. Most of the European donors do not seem to be motivated by the need of the recipient but rather by self-interest, such as colonial past. The European donors also seem to be motivated differently by the merits of the recipients.